Business Model for a Post Pandemic Startup In Indian Fast Moving Consumer Goods FMCG sector (International Journal of Scientific Research and Management (IJSRM), 2021)
The objective of this study was to come up with a Business model for the post-pandemic startup in the Indian FMCG sectors. For this purpose, a questionnaire was designed to collect the data from various respondents of different gender and age groups. The responses were taken to know what the consumers are preferring and what they choose over at the time of the pandemic. Close-ended questions were prepared to collect the data. The questions included in the questionnaire were designed in such a way that they may give a basic idea of where to hit the ball in the court at the time of the pandemic. We know that COVID-19 has shown us a picture we never thought will ever be there and were not prepared for the same. Therefore, to avoid such kind uncertainties affecting the operations of the well-settled business and also to give confidence to the start-ups that have been affected by the same this study was conducted to know the choice, preference, and other factors affecting the purchasing habits of the consumers. Through the study, we found out that the majority of the consumers are focusing more on their health and are shifting to the products which may help them to build their immunity and keep them immune from the virus. This study can be of great use for start-ups to consider and follow to make sure they grab a huge number of market shares